Hepatic granulomas in Turkey: A 6-year clinicopathological study of 35 cases - Şahin, Memduh; Yılmaz, Güldal; Arhan, Mehmet; Sen, İlker (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Granulomas are focal aggregates of modified macrophages that are surrounded by a rim of lymphocytes and fibroblasts. The present study aimed to evaluate the prevalence and etiology of hepatic granulomas (HGs) in the Department of Gastroenterology with a wider population. Materials and Methods: We performed a retrospective study on 2662 liver biopsy specimens analyzed between 2005 and 2011 at Gazi University Department of Gastroenterology to determine the presence of HGs. Results: There were 16 cases with primary biliary cirrhosis, of whom 14 without any other causative etiology. There were 6 cases of sarcoidosis, 2 cases of Fasciola hepatica infection, 2 cases of hepatitis C, and 2 cases of hepatitis B. One case had both tuberculosis and rheumatoid arthritis and one case had both tuberculosis and brucellosis. There was also one case each of leishmaniasis and Hodgkin’s lymphoma. The diagnosis of autoimmune hepatitis was found in two cases. One case had immune cholangiopathy. Conclusion: The leading causative etiology of HGs was primary biliary cirrhosis, followed by sarcoidosis. As a study performed in a center that accepts patient profiles throughout Turkey, tuberculosis took a minor part in HG etiology. A drug-affected or toxic case of HG was not observed.